Overview of Foodborne viruses: Important viruses, outbreaks, health concerns, food Handling and fresh produce - Sahar Abd Al-Daim (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2022)
Foodborne viruses can transmit through food in lots of ways including consuming items of animal origin containing zoonotic viruses, consuming contaminated food handled by infected food workers, and consuming contaminated food produced by humans. Viral foodborne illnesses are now a major contributor to all foodborne illness reports in recent years and are seen as a rising issue to the public health of humans and animals. Noroviruses and hepatitis A viruses were shown to be predominantly linked to the food-handler transmission and sewage-contaminated foods, according to microbiological research. In order to facilitate source attribution and identify risk preventive measures, routine, standard surveillance of viral outbreaks, and surveillance of virus occurrence in food products, combined with systematic strain typing, food and clinical microbiologists, would be advocated.